Pelatihan Simulasi Proteus untuk Pengendalian Peralatan Listrik Rumah pada Pemuda Muhammadiyah Cabang Pahlawan Perjuangan - Abdullah Abdullah; Cholish Cholish; Samaria Chrisna HS (Universitas Islam Negeri Sumatera Utara, 2021)
AbstractThe dedication of society carried out aims to increase the knowledge of Muhammadiyah youth groups regarding the use of technology in controlling home electrical appliances. The technology introduced by the transfer of knowledge through this service is Proteus software. The specific target of this service is that the Muhammadiyah youth group understands the use of Proteus software as a controller of electrical equipment. The method used to achieve the objectives of this Service activity is to provide training materials and demonstrate the use of the Proteus software directly, then the training participants are guided to practice directly so that they can overcome associate problems, namely associates already have knowledge related to technology-based home electrical control by utilizing simulation software. Proteus that can be used to control home electrical appliances and there is an increase in the empowerment of Muhammadiyah youth groups related to the application of technology. The stages of activities in this service are carried out by conducting associate surveys to obtain clearer information regarding associate needs. The implementation of this service activity will also be documented as data used in the final report.